“Are the Punishments Consistent?”: A Quantitative Analysis of NCAA Enforcement - Walker, Khirey; Soebbing, Brian; Seifried, Chad (Journal of Intercollegiate Sport, 2021)
Prior research on organizational misconduct within intercollegiate athletics focuses on the penalties administered by the NCAA and types of violations committed by member institutions, rather than the engagement of misconduct and the role of the NCAA as a social-control agent. Consequently, the purpose of this manuscript is to analyze the relationship between social control agents (i.e., the NCAA) and potential wrongdoers (i.e., member institutions), in addition to how the relationship affects the evolving line separating right from wrong. This quantitative study consists of a two-stage probit regression model which found evidence that the type of violations committed in major violation cases are significant in determining the likelihood of sanctions. This study will contribute to intercollegiate athletic administration by providing an opportunity to better comprehend NCAA enforcement procedures, along with utilizing the findings to discover how the NCAA functions as a social-control agent.